2004
DOI: 10.2337/diaspect.17.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Cost Savings and Clinical Effectiveness of an Extension Service Diabetes Program

Abstract: Objective. To evaluate the cost savings and clinical effectiveness of a Cooperative Extension Service diabetes education program for improving nutrition knowledge, food portioning skills, hemoglobin A 1c (A1C), and anthropometric indices.Design. Clients with type 1 or type 2 diabetes enrolled in a 3-month diabetes education course focused on food portioning skills. Pre-and postcourse anthropometric measurements, a written food portion test, an observational food portioning skill test, and an A1C test were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The findings of this study clearly support previous studies on improvement of HbA 1c levels with diabetes education beyond standard treatment alone, yet, also contribute to the limited body of knowledge surrounding methods to improve upon bundle achievement. 11 , 25 , 26 The same literature also supports the cost benefit of DSME. An economic analysis conducted in 2000 by Klonoff and Schwartz reported that for every US $1 spent on DSME, there was a net saving of $0.44 to $8.76.…”
Section: Discussionmentioning
confidence: 68%
“…The findings of this study clearly support previous studies on improvement of HbA 1c levels with diabetes education beyond standard treatment alone, yet, also contribute to the limited body of knowledge surrounding methods to improve upon bundle achievement. 11 , 25 , 26 The same literature also supports the cost benefit of DSME. An economic analysis conducted in 2000 by Klonoff and Schwartz reported that for every US $1 spent on DSME, there was a net saving of $0.44 to $8.76.…”
Section: Discussionmentioning
confidence: 68%
“…13 Studies involved patients with impaired glucose tolerance (IGT), 18,22,23,27 type 1 diabetes, 13 type 2 diabetes, 30,32,34 or both type 1 and type 2 diabetes. 10,12,14,[24][25][26]28,29,31,35 Several studies did not specify the type of diabetes. 11,[15][16][17][19][20][21]33 Study designs included meta-analysis, 26 randomized controlled trials (RCTs), 13,16,18,[22][23][24]27,34 prospective quasiexperimental pre-post studies, [10][11][12]14,15,20,25,29 and retrospective database analyses.…”
Section: Resultsmentioning
confidence: 99%
“…10,12,14,[24][25][26]28,29,31,35 Several studies did not specify the type of diabetes. 11,[15][16][17][19][20][21]33 Study designs included meta-analysis, 26 randomized controlled trials (RCTs), 13,16,18,[22][23][24]27,34 prospective quasiexperimental pre-post studies, [10][11][12]14,15,20,25,29 and retrospective database analyses. 17,19,21,28,30,[31][32][33]35 The studies conducted cost analyses, 13,19,22,28,29,32 cost-effectiveness analyses, [10]...…”
Section: Resultsmentioning
confidence: 99%
“…Regularly using the skill of accurate food portioning has been shown to be cost-effective in managing diabetes. 11 The community diabetes program, 11 which emphasized food portioning skills, label reading, and cooking skills, showed a significant decrease in hemoglobin A 1c and a significant cost savings in hospital charges according to the scale set by Gilmer et al 12 In addition to accurate portioning skills, it is also important to consider convenience and family influences on dietary, caloric, and carbohydrate intake. The results of this study were similar to one assessing the nutrient Feature Article/Christensen et al…”
Section: Discussionmentioning
confidence: 99%